Optimization of Electric Power Flow Analysis Using the Gauss-Seidel Method in a Numerical Approach - E, Erwin; Arifin, Ilham; Panjaitan, Septhia Eka Nurviranthy; Manik, Graceya Zagita; Marsela, Wiwi; Manurung, Janter Ricardo (Information Technology and Science (ITScience), 2025)
The availability of electrical energy is a fundamental requirement in modern society, supporting both daily life and industrial activities. To ensure efficient and reliable energy distribution, power flow analysis is critical. This analysis is grounded in Kirchhoff's laws, which serve as the foundation for understanding electrical circuits. Kirchhoff's Current Law (KCL) states that